2008
DOI: 10.1902/jop.2008.070321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Anti‐Cardiolipin and Oxidized Low‐Density Lipoprotein Levels in Chronic Periodontitis Patients With Essential Hypertension

Abstract: Background: The aim of the present study was to investigate whether chronic periodontitis caused the elevated levels of anti‐cardiolipin antibodies (anti‐CL) and oxidized low‐density lipoprotein (oxLDL) in subjects with essential hypertension. Methods: Seventy‐two subjects were categorized as healthy controls, subjects with essential hypertension and periodontal health (healthy‐hypertension group), subjects with essential hypertension and gingivitis (gingivitis‐hypertension group), or subjects with essential h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Following a report in 2003 by Sheinkin et al [90] that aCL were found in up to 20 % of patients with chronic periodontitis and generalized aggressive periodontitis, Türkoğlu et al [91] confirmed that mean IgM aCL levels and the prevalence of subjects positive for IgM anti-CL were significantly higher in their periodontitis-hypertension group compared to the other groups with hypertension. In a 2007 study, Sheinkin et al…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 92%
“…Following a report in 2003 by Sheinkin et al [90] that aCL were found in up to 20 % of patients with chronic periodontitis and generalized aggressive periodontitis, Türkoğlu et al [91] confirmed that mean IgM aCL levels and the prevalence of subjects positive for IgM anti-CL were significantly higher in their periodontitis-hypertension group compared to the other groups with hypertension. In a 2007 study, Sheinkin et al…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 92%
“…Furthermore, Turkoglu (Turkoglu et al 2008) demonstrated that periodontitis patients with hypertension have elevated IgM anti-CL serum antibodies and speculated that these antibodies may impart increased risk for atherosclerosis in these patients. Finally, Pussinen (Pussinen et al 2004b) noted that in patients with severe periodontitis and high serum LPS concentrations, periodontal therapy resulted in a decrease in serum anti-b2GP1 concentration, implicating gram negative bacterial infection in the production of antib2GP1 in periodontitis.…”
Section: Anti-cardiolipinmentioning
confidence: 99%
“…Periodontitis subjects also have antibodies against lipids and lipoproteins. For example, the prevalence of β2-glycoprotein-dependent anticardiolipin is elevated in both chronic and aggressive periodontitis [155,167,168]. Other studies indicate that anti-oxLDL antibodies are elevated in subjects with periodontitis [111,169].…”
Section: Periodontal Disease Lipoproteins and Lipoprotein Metabolismmentioning
confidence: 99%